Allogeneic Umbilical Cord Blood Infusion for Adults with Ischemic Stroke: Clinical Outcomes from a Phase I Safety Study. (12th May 2018) - Laskowitz, Daniel T.; Bennett, Ellen R.; Durham, Rebecca J.; Volpi, John J.; Wiese, Jonathan R.; Frankel, Michael; Shpall, Elizabeth; Wilson, Jeffry M.; Troy, Jesse; Kurtzberg, Joanne
Abstract : Stroke is a major cause of death and long-term disability, affecting one in six people worldwide. The only currently available approved pharmacological treatment for ischemic stroke is tissue plasminogen activator; however, relatively few patients are eligible for this therapy. We hypothesized that intravenous (IV) infusion of banked unrelated allogeneic umbilical cord blood (UCB) would improve functional outcomes in patients with ischemic stroke. To investigate this, we conducted a phase I open-label trial to assess the safety and feasibility of a single IV infusion of non-human leukocyte antigen (HLA) matched, ABO matched, unrelated allogeneic UCB into adult stroke patients. Ten participants with acute middle cerebral artery ischemic stroke were enrolled. UCB units were matched for blood group antigens and race but not HLA, and infused 3–9 days post-stroke. The adverse event (AE) profile over a 12 month postinfusion period indicated that the treatment was well-tolerated in these stroke patients, with no serious AEs directly related to the study product. Study participants were also assessed using neurological and functional evaluations, including the modified Rankin Score (mRS) and National Institute of Health Stroke Scale (NIHSS). At 3 months post-treatment, all participants had improved by at least one grade in mRS (mean 2.8 ± 0.9) and by at least 4 points in NIHSS (mean 5.9 ± 1.4), relative to baseline. Together, these data suggest that a single i.v. dose of allogeneic non-HLA matched human UCB cells is safe in adults with ischemic stroke, and support the conduct of a randomized, placebo-controlled phase 2 study.